HERMENEUTIC-NOEMATIC DEPENDENCY OF LEXEME SOUND COMPOSITION - Sergey Bredikhin (Гуманитарные и юридические исследования)
The article deals with potentialities of noematic structuring of sound complexes within the frame of phonosemantics; it claims their direct dependence on linguoculture code of hetero-structured languages. The article describes certain quanta of underlying noematic phoneme content with the reference to Russian linguoculture.